Rumen microbiota responses to the enzymatic hydrolyzed cottonseed peptide supplement under high-concentrate diet feeding process - Ma, Peng; Hong, Yifen; Liu, Chunxue; Sun, Yuqin; Liu, Minze; Yang, Zhengang; Ma, Pengyun; Wu, Hongxiang; Xue, Fuguang (Frontiers in Veterinary Science, 2022)
In current dairy production, dietary energy is always excessively provided with a high-concentrate diet feeding to improve milk production. However, this feeding practice disturbed the rumen microbial ecosystem and the balance between ruminal energy and nitrogen, resulting in decreased nutrient fermentability, which in turn declined the milk yield of dairy cows. Therefore, supplementation of dietary degradable nitrogen may be helpful for high dairy production. In this study, we evaluated the regulatory effects of easily utilized enzymatic hydrolyzed cottonseed peptide (EHP) supplements on rumen microbiota communities and rumen nutrient fermentability under high-concentrate feeding. For this purpose, a gradient concentrate of EHP (from 0.2 to 1.0%) was added to the high-concentrate basal substrates for an in vitro experiment. Each treatment contained three replicates, with three bottles in each replicate. Rumen fermentable parameters included microbial protein content, volatile fatty acids, and ammonia-N; the rumen nutrient degradability of dry matter, crude protein, neutral detergent fiber, acid detergent fiber, ether extracts, calcium, and phosphorus were further investigated after in vitro fermentation for 72 h. Then, rumen microbiota communities and their correlation with ruminal fermentation parameters and rumen nutritional degradability were analyzed to understand the regulatory mechanism of the EHP supplements on rumen fermentability. Results indicate that treatment with 0.6% of EHP supplements had the highest content of acetate, butyrate, and neutral detergent fiber degradability among all treatments. Furthermore, EHP supplements significantly increased the relative abundance of rumen cellulose and starch-degrading bacteria such as Ruminococcus, Bifidobacterium, and Acetitomaculum, and the high nitrogen utilizing bacteria Butyrivibrio and Pseudobutyrivibrio, which may further promote the rumen carbohydrate and nitrogen metabolism. In summary, supplementation of easily degraded small peptides helps reestablish rumen energy and nitrogen balance to promote the rumen fermentable functions and nutritional degradability under high-concentrate diet feeding circumstances. These findings may further promote dairy production.